A Comparative study on protection of Cyclopia spp. (Honeybush), Aspalathus linearis (Rooibos) and Camellia sinensis teas against Aflatoxin B1 induced mutagenesis in the Salmonella Mutagenicity assay : possible mechanisms involved - Van der Merwe, J. D. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (Msc Food Sc (Food Science))--University of Stellenbosch, 2005.